Ancestral QTL Alleles from Wild Emmer Wheat Enhance Root Development under Drought in Modern Wheat - Merchuk-Ovnat, Lianne; Fahima, Tzion; Ephrath, Jhonathan E.; Krugman, Tamar; Saranga, Yehoshua (Frontiers in Plant Science, 2017)
A near-isogenic line (NIL-7A-B-2), introgressed with a quantitative trait locus (QTL) on chromosome 7AS from wild emmer wheat (Triticum turgidum ssp. dicoccoides) into the background of bread wheat (Triticum aestivum L.) cv. BarNir, was recently developed and studied in our lab. NIL-7A-B-2 exhibited better productivity and photosynthetic capacity than its recurrent parent across a range of environments. Here we tested the hypothesis that root-system modifications play a major role in NIL-7A-B-2's agronomical superiority. Root-system architecture (dry matter and projected surface area) and shoot parameters of NIL-7A-B-2 and 'BarNir' were evaluated at 40, 62 and 82 days after planting (DAP) in a sand-tube experiment, and root tip number was assessed in a ‘cigar-roll’ seedling experiment, both under well-watered (WW) and water-limited (WL) treatments. At 82 DAP, under WL treatment, NIL-7A-B-2 presented greater investment in deep roots (depth 40-100 cm) than 'BarNir', with the most pronounced effect recorded in the 60–80 cm soil depth (60% and 40% increase for root dry matter and surface area, respectively). NIL-7A-B-2 had significantly higher root-tip numbers (~48%) per plant than 'BarNir' under both treatments. These results suggest that the introgression of 7AS QTL from wild emmer wheat induced a deeper root system under progressive water stress, which may enhance abiotic stress resistance and productivity of domesticated wheat.